2023
DOI: 10.1186/s12866-023-02762-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets with different amino acid release characteristics on the gut microbiota and barrier function of weaned pigs

Abstract: Background The absorption and utilization of proteins by animals is affected by the amino acid (AA) release characteristics of their diets. In the present study, we aimed to determine the effects of diets with various amino acid release characteristics on the intestinal barrier function and diversity of gut microbiota of weaned pigs. Results Forty-eight pigs (7.45 ± 0.58 kg) were fed with diets having different amino acid release characteristics du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The prediction in this meta-analysis about functional profiling of the bacterial communities revealed that bacteria associated with metabolic processes, such as starch, sucrose, and amino acid metabolism, were more abundant in pigs fed the SDPP diet. Prior research has demonstrated that enhancements in the amino acid metabolism pathway levels are regarded as a reliable predictor of more efficient utilization of dietary protein [40,41]. One of the prevalent bacteria affected by SDPP was Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction in this meta-analysis about functional profiling of the bacterial communities revealed that bacteria associated with metabolic processes, such as starch, sucrose, and amino acid metabolism, were more abundant in pigs fed the SDPP diet. Prior research has demonstrated that enhancements in the amino acid metabolism pathway levels are regarded as a reliable predictor of more efficient utilization of dietary protein [40,41]. One of the prevalent bacteria affected by SDPP was Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…Strong intestine anti-inflammatory activity is exhibited by indole, the most prevalent microbial metabolite of aromatic amino acids, and its anti-inflammatory mechanism has been extensively researched [ 165 , 166 ]. A recent study on the effects of diets with different amino acid release properties on the gut microbiota of weaned pigs revealed that the diversity of the gut microbiota was increased by the balanced release of amino acid diets [ 167 ]. Furthermore, Zhao and his colleagues highlighted that dietary protein’s source, level, and amino acid balance of dietary protein primarily influence its composition, shape, and function.…”
Section: Large Intestinementioning
confidence: 99%
“…The absorption and utilization of proteins in pigs is influenced by the AA availability in the diet ( Mi et al, 2023 ). Different protein sources exhibit various patterns of AAs release, that are influenced by the solubility and digestibility of the protein ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diets with lower standardized ileal digestibility resulted in greater microbial diversity and an increased abundance of Lactobacillus in the jejunum. Casein or mix diet as protein source led to a higher microbial diversity in the jejunum than the diet with corn gluten meal through the equalized release of AAs ( Mi et al, 2023 ). A dietary crude protein (CP) content of 12% led to lower growth performance in pigs combined with lower abundance of Prevotella , while Christensenellaceae , Aligiphilus , and Algoriphagus were more abundant in the pig feces ( Spring et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%